In God We Trust: The Prospects for the Future of Islam and the West Are Positive (American Journal of Islam and Society, 2005)
Question 1: Who are the moderate Muslims, and what are their beliefs andpolitics?FAR: The debate among the participants shows that while the term moderateMuslim is problematic, there is a need to define the attitudinal differencebetween Muslims who can be worked with from those who cannot. Isuggest that the defining feature is between those who believe in a pluralist,multicultural, multi-religious societal contract that allows for differencesof opinions within an over-arching construct, as opposed to thosewho believe in a societal contract that has no space for other religions, ethnicities,or cultures, or even intra-Islamic differences of opinion.1The latter attitude leads to the phenomenon known as “Islamist terrorism,”the modern-day version of the seventh-century Kharijites, who foughtand ultimately assassinated Ali, Prophet Muhammad’s son-in-law, and who,over the following century, developed a political philosophy that justifiedmurdering fellow Muslims, including innocent women and children.Contemporary Muslims need to support that aspect of the war on terror thatis a true jihad against all forms of terrorism, known in classical Islamicjurisprudence as hirabah, and anarchic terrorism that tears the social fabricessential to well-functioning societies. But this cannot be done withoutsimultaneously purging Muslim societies of some other modern “isms” thathave “terrorized” Muslims and still continue to deny them their inalienablehuman rights under the Shari`ah.2One is fascism in the Muslim world, whether wrapped in a secularveneer like that of Saddam Hussein in Iraq or in an Islamic veneer like thatof the Taliban in Afghanistan. Another is nationalism, a modernized formof pre-Islamic tribalism that Muslim theologians call `asabiyah and thatmore properly belongs to the jahili (pre-Islamic) time. This idea can morphinto the modern form of Islamic nationalism that, in turn, leads to religiousauthoritarianism, which oppresses those Muslims and non-Muslims whofollow authentic and legitimate religious interpretations that dare to differfrom the “official” versions, and brands anyone who does not accept itspoint of view as an infidel, thereby arrogating to itself a right that theProphet declared belongs only to God ...